Chronic ulcerative colitis. Suppurative pericarditis. Abdominal pericardiectomy - Zagia, Miguel; Cassinelli, Daniel (Cirugía del Uruguay, 1972)
The paper describes a case of acule pericarditis requiring drainage of the pericardium in a patient suffering from chronic ulcerative colitis. Emphasis is laid on the approach and the reasons that lead to it. The correct evolution of the patient is pointed out.